Tools for Working with Guidelines Annual Meeting of the Special Interest Group - Vanderdonckt, Jean; Farenc, Christelle (Springer London, 2001)
This volume contains the papers presented at the International Workshop on Tools for Working with Guidelines, (TFWWG 2000), held in Biarritz, France, in October 2000. It is the final outcome of the International Special Interest Group on Tools for Working with Guidelines. Human-computer interaction guidelines have been recognized as a uniquely relevant source for improving the usability of user interfaces for interactive systems. The range of interactive techniques exploited by these interactive systems is rapidly expanding to include multimodal user interfaces, virtual reality systems, highly interactive web-based applications, and three-dimensional user interfaces. Therefore, the scope of guidelines' sources is rapidly expanding as well, and so are the tools that should support users who employ guidelines to ensure some form of usability. Tools For Working With Guidelines (TFWWG) covers not only software tools that designers, developers, and human factors experts can use to manage multiple types of guidelines, but also looks at techniques addressing organizational, sociological, and technological issues